1999
DOI: 10.1159/000025672
|View full text |Cite
|
Sign up to set email alerts
|

Local Adenovirus-Mediated Delivery of Hirudin in a Rabbit Arterial Injury Model

Abstract: Intravascular delivery of an E1/E3 deleted adenovirus encoding the hirudin protein reduces neointimal formation in the rat arterial injury model. Given the interspecies variability in response to adenoviral vectors, we tested this same construct in the hirudin-sensitive cholesterol-fed rabbit arterial balloon injury model. We hypothesized that local delivery of an E1/E3-deleted adenovirus encoding hirudin (Ad-Hir) in addition to early hirudin infusion would limit neointimal formation compared to early hirudin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…14 The injury score of each artery was assessed with the following scale: 0, intact internal elastic lamina (IEL); 1, lacerated IEL, compression of media; 2, lacerated IEL and media; and 3, large transluminal laceration including disruption of the EEL. 14 …”
Section: Quantitative Histomorphometrymentioning
confidence: 99%
See 1 more Smart Citation
“…14 The injury score of each artery was assessed with the following scale: 0, intact internal elastic lamina (IEL); 1, lacerated IEL, compression of media; 2, lacerated IEL and media; and 3, large transluminal laceration including disruption of the EEL. 14 …”
Section: Quantitative Histomorphometrymentioning
confidence: 99%
“…Paraffin-embedded sections were stained with the following antibodies: HHF-35, a mouse monoclonal anti-human ␣-actin, 0.3 g/mL (Enzo Diagnostics); RAM-11, mouse monoclonal anti-rabbit macrophage, 1.2 g/mL (Dako Corp) 14 ; polyclonal goat anti-rabbit T cell, 4 g/mL (Accurat Chem) 14 ; and polyclonal goat anti-mouse PECAM-1 (platelet and endothelial cell adhesion molecule-1), 1 g/mL (Santa Cruz Biotechnology, Inc). 15 Before labeling with T-cell or PECAM-1 antibodies, arterial tissue underwent microwave antigen retrieval (Vector Labs).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, this study demonstrated that adenoviral-mediated secretion of hirudin from ECs lining implanted femoral AVGs not only significantly reduced the proliferation of VSMCs but also the aggregation of platelets, formation of thrombus, and platelet deposition. Similar experiments testing the efficacy of hirudin to inhibit neointimal formation have been performed in the rat arterial injury model and cholesterol-fed rabbit arterial balloon-injury model (8). E1/E3-deleted adenoviral-mediated delivery of hirudin into the rabbit model resulted in a 79% reduction in vessel wall thrombin activity at 48 h after balloon angioplasty.…”
Section: Thrombosismentioning
confidence: 74%
“…Genetic approaches to increase thromboresistance have been achieved by multiple groups through the overexpression of thrombomodulin [115], hydrolysis of adenosine nucleotides [116], addition of an ADPase [117], plasmin induction [118] or activators [119], and hirudin [120,121]. Of course, ECs themselves secrete many of these substances endogenously [122,123], so these approaches may be no more effective than a functioning endothelium, and thus, they may be best applied to SMCs or non-cellular prosthetic systems that are not expected to endothelialize over time.…”
Section: Inhibiting Thrombosis Through Ec Gene Deliverymentioning
confidence: 99%